(untitled) (Nigerian Journal of Technology, 2021)
Every tertiary academic institution has the obligation of recording and taking the attendance of its students during lecture periods. Over the years the process and accuracy of this attendance has been marred by many challenges which range from the cumbersome nature of paper sheets used in recording, to the manipulation of attendance by unscrupulous students and so on. This paper is aimed at designing and implementing a biometric students’ time and attendance logging system that helps in mitigating these challenges. This biometric student time and attendance logging system uses the fingerprint biometric characteristics to accurately identify the student. The system also generates a report showing the number of times a particular student was present or absent in a semester. This feat was achieved through the use of an atmega328P microcontroller, a fingerprint RS305 module, a liquid crystal display (LCD), a Red Green Blue (RGB) light emitting diode (LED) and a Personal Computer (PC) amongst others. The software used in this work was developed using visual studio C# and MySQL2008, and the final work was simulated using proteus before it was constructed and tested. The results of the test show a significant improvement over the manual attendance system. http://dx.doi.org/10.4314/njt.v40i3.14